TINDAK PIDANA PEMALSUAN STIKER BPOM PADA PRODUK PANGAN DILIHAT DARI PERSFEKTIF HUKUM PIDANA ADMINISTRASI - Asmita, Anes Sefta (The Juris, 2025)
This study aims to examine the criminal law regulations regarding the crime of forgery of Distribution Permits, namely forgery of BPOM stickers and SNI Logos and their impact on consumers by looking at the perspective of consumer protection laws regulated in administrative criminal law. Recently, a case of forgery of BPOM stickers for one of the food products, namely Minyakita, was found, which of course will have an impact on consumers and has the potential to endanger buyers of the food product if it is proven that the food product using the fake BPOM sticker is not suitable for consumption because it does not go through a proper distribution permit and laboratory tests. Criminal Law has an important role in supporting consumer protection measures in addition to consumer protection laws, and which will also be studied in more depth from the perspective of administrative criminal law. This study uses a normative juridical research method with a judicial case study approach method and uses secondary data in data collection.